Pengembangan Aplikasi Simulasi Berbasis Web terhadap Kompetensi Kognitif Crimping Kabel UTP Siswa SMK - Wibawa, Ramadhan Cakra; Baihaqi, Ahmad Zulkifli; Herlambang, Yudha Bima; Rahmawati, Cahya Dwi; Pratama, Muhammad Angga (Jurnal Kridatama Sains dan Teknologi, 2025)
In the field of computer networks and telecommunications, one of the basic skills that must be mastered is the installation of UTP (Unshielded Twisted Pair) cables. This skill is the main foundation in building network systems. However, in practice, the learning process often faces obstacles. Limited practice equipment, the risk of student errors that can cause equipment damage, and short learning times make it difficult for students to understand the concept in depth. This condition causes some students to have difficulty understanding the procedures and logic of UTP cable installation. To address these challenges, this study developed and tested a web-based simulation application called "Crosslink". This application is designed to provide an interactive learning experience without the risk of device damage. This study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, and Disseminate) which aims to produce valid, practical, and effective learning products. There are two types of validators, namely material experts and media experts. Material experts’ assessments measure content suitability, while media experts’ assessments refer to ISO 25010, and user response testing uses the Technology Acceptance Model (TAM) parameters. This study involved 35 students majoring in Computer Networking (TKJ) at SMK Ketintang Surabaya as respondents. The validation results from material experts were 86.67% and from media experts were 81.67%, indicating that the application meets software quality standards and is suitable for use in learning. Meanwhile, the user response results reached 80.47%, indicating that the application is easy to use in learning the UTP cable crimping process. These findings indicate that Crosslink not only meets the technical feasibility aspect, but also supports learning based on cognitive load theory by helping students focus on understanding crimping concepts without the risk of practical errors.